The big deal about Little League ; Changing roles ; Prime time [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
A debate on the controversy of Philippines representatives on Little League International. Looks at surgical sex change among homosexuals. Features also the new and promising talents of onnie Henares Prime Line: Patricia and Tiny.
The big deal about Little League (12 min.) -- Changing roles (15 min.) -- Prime time (16 min.)
VHS.
Keywords: Little League Baseball; Baseball for children, Corrupt practices; Homosexuality, Male -- Philippines; Gay men -- Philippines; Acting -- Auditions -- Philippines; Singing -- Auditions -- Philippines